AG-NGS: A powerful and user-friendly computing application for the semi-automated preparation of next-generation sequencing libraries using open liquid handling platforms - Sergio Callejas; Rebeca Álvarez; Alberto Benguria; Ana Dopazo (BioTechniques)
Protocol Summary We have developed automatic genomics NGS (AG-NGS), a computing application that allows an open liquid handling platform to be transformed into a library preparation station without losing the potential of an open platform. Implementation of AG-NGS does not require programming experience, and the application has also been designed to minimize implementation costs. Automated library preparation with AG-NGS generated high-quality libraries from different samples, demonstrating its efficiency, and all quality control parameters fell within the range of optimal values.